Application of geographic information system (GIS) for potential productivity evaluation of lowland rice area in Chachoengsao Province, Thailand - Pongnak, W.; Badayos, R. B. (1995)
The study was conducted to characterize land quality attributes of lowland rice areas from spatial and non-spatial data using GIS technology, test the application of FAO and soil taxonomy framework to determine the inherent and potential productivity of major soil series for lowland rice production, and validate the results of GIS processing by comparing the predicted yields from the actual yield of farmers.

Land suitability and productivity evaluations of lowland rice areas in Chachoengsao Province, Thailand were made using spatial and non-spatial data of soil, land use and climate according to the FAO and soil taxonomy framework. These data were inputted, stored and manipulated to generate the suitability and productivity ratings of soils, particularly of paddy farms with the aid of a GIS called SPANS GIS.

Based on the FAO framework, 28.73% of the total lowland rice area of Chachoengsao Province may be classified under class 2 in both suitability and inherent productivity. Furthermore, productivity can be improved from class 2 to class 1 (excellent productivity) with proper management. Using the soil taxonomy framework, the productivity ratings were generally higher compared to the ratings obtained from the FAO framework resulting in higher predicted yields. It was also noted that areas with excellent inherent productivity of about 28.34% of the total area could possibly be raised to 39.32% with correct inputs.
The validation of GIS processing revealed that in both FAO and soil taxonomy productivity evaluation frameworks, the predicted inherent yields were higher in relation to the actual yields obtained by the farmers with coefficient of correlation computed at 0.64 and 0.70, respectively.
Keywords: Geographic Information Systems; Soil productivity